A Conversation That Never Was: Del Noce and Vattimo on Atheism, Secularization, and Nihilism - Markevičius, Domantas (Religija ir kultūra, 2017)
[full article and abstract in Lithuanian; abstract in English]This paper questions the interpretation of Augusto Del Noce’s and Gianni Vattimo’s views on secularization and nihilism that was offered by Roberto Esposito; it also suggests an alternative assessment of their conflicting relation. It compares the considerations on modernity and atheism, offered by both Del Noce and Vattimo, attempting to explain in what particular mode their views on secularization and nihilism essentially differ. It concludes that Esposito assesses the conflicting nature between Del Noce’s and Vattimo’s philosophies inadequately: Del Noce’s interpretation of modernity and atheism should be seen not as dissolving in Vattimo’s weak thought but rather as an important sign of the plurality of ways when dealing with the phenomena of secularization and nihilism as characteristic of contemporary Italian philosophy.
Keywords: Del Noce; atheism; Vattimo; nihilism; secularization